2017
DOI: 10.1038/tp.2017.196
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-3 modulates the structural plasticity of dentate granule cells and long-term memory

Abstract: Nectin-3, a cell adhesion molecule enriched in hippocampal neurons, has been implicated in stress-related cognitive disorders. Nectin-3 is expressed by granule cells in the dentate gyrus (DG), but it remains unclear whether nectin-3 in DG modulates the structural plasticity of dentate granule cells and hippocampus-dependent memory. In this study, we found that DG nectin-3 expression levels were developmentally regulated and reduced by early postnatal stress exposure in adult mice. Most importantly, knockdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…We found that suppression of nectin‐3 in hippocampus from early postnatal stage mimicked early‐life stress effects, impairing novel object recognition that mainly depends on the neuronal network between hippocampus and perirhinal cortex, and spatial object recognition memory which is specifically regulated by the hippocampus (Cohen et al, ; Lupien et al, ). In addition, consistent with other findings, short‐term spatial working memory evaluated by the Y‐maze spontaneous alternation behavior was not significantly altered in mice with nectin‐3 knockdown (Wang et al, , ). These results suggest that nectin‐3 may be partially involved in hippocampus‐dependent memory functions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that suppression of nectin‐3 in hippocampus from early postnatal stage mimicked early‐life stress effects, impairing novel object recognition that mainly depends on the neuronal network between hippocampus and perirhinal cortex, and spatial object recognition memory which is specifically regulated by the hippocampus (Cohen et al, ; Lupien et al, ). In addition, consistent with other findings, short‐term spatial working memory evaluated by the Y‐maze spontaneous alternation behavior was not significantly altered in mice with nectin‐3 knockdown (Wang et al, , ). These results suggest that nectin‐3 may be partially involved in hippocampus‐dependent memory functions.…”
Section: Discussionsupporting
confidence: 89%
“…Nectins as CAMs locate at the synaptic sites in neuronal axons and dendrites and play an important role in the formation of synapses by altering the spine number and size which is crucial to learning processes (Mizoguchi et al, ; Takai et al, ; Wang et al, ). Abnormal nectin expression has been observed in stressed mice, which may mediate stress‐induced impairments in hippocampus‐dependent memory and structural plasticity (Liao et al, ; van der Kooij et al ; Wang et al, , ). In the present study, we directly examined the causal involvement of nectins in hippocampal neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nectin-3 knockdown in adult hippocampus was previously shown to decrease dendritic spine densities relative to control 18,20 . In contrast, we show here that nectin-3 knockdown at E15.5 in L2/3 visual cortical neurons increased dendritic spine densities relative to control at P21, but not at P14 or P35.…”
Section: Discussionmentioning
confidence: 94%
“…For example, axonal (presynaptic) nectin-1 in dentate granule cells specifically binds to dendritic (postsynaptic) nectin-3 in CA3 principal neurons at the stratum lucidum in hippocampus to help guide and stabilize developing synaptic connections between these neurons ( Figure 1A) 10,14 . Other studies have implicated nectins in a variety of biological and disease states, including long-term memory formation, stress, taopathy, and mental retardation, indicating that nectins may have different functions in the development, aging, and maintenance of various brain circuits [16][17][18][19][20] . While previous work suggests that nectin-1 and nectin-3 may be involved in both the formation and maturation (stabilization) of synapses in hippocampus, their function in postnatal cortical development is unknown 14 .…”
Section: Introductionmentioning
confidence: 99%